Giving women alliance and exchange in Victorian culture - Rappoport, Jill. (New York : Oxford University Press, 2012)
Drawing on novels, poetry, periodicals, and political pamphlets 'Giving Women' examines the literary expression and cultural consequences of gift exchange among English women from the 1820s until the end of the First World War.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Includes bibliographical references and index.
Keywords: English literature -- 19th century -- History and criticism; English literature -- Women authors -- History and criticism; Generosity in literature; Women and literature -- England -- History -- 19th century; Literature and society -- England -- History -- 19th century; Women in literature; Women and literature -- England -- History -- 20th century; Literature and society -- England -- History -- 20th century